Dopaminergic Treatment Effects on Dysarthric Speech: Acoustic Analysis in a Cohort of Patients With Advanced Parkinson's Disease - Cavallieri, Francesco; Budriesi, Carla; Gessani, Annalisa; Contardi, Sara; Fioravanti, Valentina; Menozzi, Elisa; Pinto, Serge; Moro, Elena; Valzania, Franco; Antonelli, Francesca (Frontiers in Neurology, 2021)
Importance: The effects of dopaminergic treatment on speech in patients with Parkinson’s disease (PD) are often mixed and unclear. The aim of this study was to better elucidate those discrepancies. Methods: Full retrospective data from advanced PD patients before and after an acute levodopa challenge were collected. Acoustic analysis of spontaneous monologue and sustained phonation including several quantitative parameters (i.e. maximum phonation time [MPT]; Shimmer Local dB) as well as the Unified Parkinson's Disease Rating Scale (UPDRS) (total scores, subscores and items) and the Clinical Dyskinesia Rating Scale (CDRS) were performed in both the defined-OFF and -ON conditions. The primary outcome was the changes of speech parameters after levodopa intake. Secondary outcomes included the analysis of possible correlations of motor features and levodopa-induced dyskinesia (LID) with acoustic speech parameters. Statistical analysis included paired t-test between the ON and OFF data (calculated separately for male and female subgroups), and Pearson correlation between speech and motor data. Results: In 50 PD patients (male: 32; female: 18), levodopa significantly increased the MPT of sustained phonation in female patients (p<0.01). In the OFF-state, the UPDRS part-III speech item negatively correlated with MPT (p=0.02) whereas in the ON-state, it correlated positively with the Shimmer Local dB (p=0.01), expression of poorer voice quality. The total CDRS score and axial subscores strongly correlated with the ON-state Shimmer Local dB (p= 0.01, p< 0.01, respectively). Conclusions: Our findings emphasize that levodopa has poor effect on speech acoustic parameters. The intensity and location of LID negatively influenced speech quality.